Community-Based Monitoring of Oil Extraction: Lessons Learned in the Ecuadorian Amazon. Issue 3 (3rd March 2020) - Mena, Carlos F.; Arsel, Murat; Pellegrini, Lorenzo; Orta-Martinez, Marti; Fajardo, Pablo; Chavez, Ermel; Guevara, Alexandra; Espín, Paola
Abstract: This paper reports on an ongoing initiative that seeks to enhance the detection, monitoring, and reporting capabilities of local communities in the Northern Ecuadorian Amazon through the introduction of hardware and digital tools, as a strategy to strengthen their ability to produce socio-environmental evidence. A Community Based Monitoring (CBM) system has been created to link social organizations, fighting for environmental justice, and academics working on the region in topics related to oil extraction and environmental change. This paper first, conceptualize the need for rural participatory systems of data collection, analysis, and distribution of environmental liabilities in extractive frontiers. Second, the paper provides a description of this community monitoring system in the Ecuadorian Amazon, in a way that can be used by communities and researchers in different contexts. Finally, the paper reflects on lessons learned to understand the main challenges and opportunities of similar systems.